Drift-dependent changes in iceberg size-frequency distributions - Kirkham, James D.; Rosser, Nick J.; Wainwright, John; Vann Jones, Emma C.; Dunning, Stuart A.; Lane, Victoria S.; Hawthorn, David E.; Strzelecki, Mateusz C.; Szczuciński, Witold (Nature Publishing Group, 2017)
Although the size-frequency distributions of icebergs can provide insight into how they disintegrate, our understanding of this process is incomplete. Fundamentally, there is a discrepancy between iceberg power-law size-frequency distributions observed at glacial calving fronts and lognormal size-frequency distributions observed globally within open waters that remains unexplained. Here we use passive seismic monitoring to examine mechanisms of iceberg disintegration as a function of drift. Our results indicate that the shift in the size-frequency distribution of iceberg sizes observed is a product of fracture-driven iceberg disintegration and dimensional reductions through melting. We suggest that changes in the characteristic size-frequency scaling of icebergs can be explained by the emergence of a dominant set of driving processes of iceberg degradation towards the open ocean. Consequently, the size-frequency distribution required to model iceberg distributions accurately must vary according to distance from the calving front.
Keywords: iceberg; Greenland; seismology; glaciology; physical oceanography; passive seismology; iceberg drift; iceberg degradation